PENGARUH INTENSITAS PERSEDIAAN DAN KOMITE AUDIT TERHADAP TARIF PAJAK EFEKTIF (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Jati, Sri Kuntoro; Karlina, Lilis (LPPM Universitas Bina Bangsa, 2025)
This research aims to provide emprical evidence that there is an influence of the Inventory Intensity and Audit Committee on Effective Tax Rate in Energy sector companies listed on the IDX (Indonesia Stock Exchange) for the period 2019 -2023. The sampling technique used was purposive sampling, where from 87 Energy Companies a sample of 22 companies was obtained for 5 years so that a total of 110 data samples were obtained. The method used is multiple linear regression, descriptive statistical test, panel data regression model analysis, Random Effect Model selection test, classical assumption test, multiple linear test and hypothesis test with the help of e-views version 12 statistical data processing. The results of this research show that Inventory Intensity and Audit Committee simultaneously have a significant effect on Effective Tax Rate and the t-test states that Inventory Intensity has a significant effect on Effective Tax Rate. The variables Audit Committee have no effect significant to Effective Tax Rate.